Factors influencing river discharge variability in the Himalayan mountain region: a case study of two catchments with contrasting geographical settings - Tuladhar, Dinesh (Curtin University, 2021)
This study examined variabilities in precipitation, temperature, river discharge and land use/land cover in two of the Ganges sub-catchments in the Himalayan mountains region of Nepal using historical data between 1970 and 2017. Urban land increased substantially in Bagmati catchment while snow/glacier cover decreased in the Marsyangdi catchment. Precipitation showed decreasing trend while minimum and maximum temperatures as well as diurnal temperature range were increasing. Consequently, river discharge in Bagmati catchment was decreasing but was increasing in Marsyangdi basin.